Consumer and Community Protection in the Banking Financial Services Sector - Hirsanuddin; Ida Surya; Kumiawan Kumiawan; Nikmah Mentari (Faculty of Law, University of Mataram, 2026)
The purpose of this study is to find and discover new legal theories and norms related to the legal protection of consumers and society in the banking financial services sector; the role of the state in contributing to the legal protection of consumers and society in the banking financial services sector, and the resolution of disputes between financial service actors and consumers of banking financial services who are harmed. The method used in this study is Normative legal research using a conceptual approach, legislation, by conducting a literature study. The legal materials obtained are analyzed using qualitative analysis methods. The role of the Financial Services Authority is not limited to facilitating consumer protection, which accommodates and becomes a mediation institution, but also becomes an institution that takes sides with consumers in the form of legal defense activities, the forms of protection carried out by the Financial Services Authority include efforts to prevent violations and restore consumer rights if there is a loss experienced by consumers. The resolution of disputes between financial service actors and consumers of banking financial services is carried out by the Indonesian Banking Dispute Resolution Alternative Institution (LAPSI). Consumer protection in the financial services sector constitutes an integrated framework encompassing the Consumer Protection Law and the OJK Law, with the OJK acting as the primary regulator responsible for both preventive and enforcement functions, though dispute resolution has largely been delegated to LAPS, creating normative inconsistencies. Bank liability for customer losses, including those arising from electronic banking, is grounded in fault-based liability principles (tort and breach of contract), with obligations to ensure system security and a tendency for the burden of proof to shift to the bank. The enactment of POJK 2022 further narrows the OJK’s role to regulation and supervision, while dispute resolution is predominantly managed by LAPS, thereby diminishing OJK’s direct facilitative function and its position as a buffer institution. To address these challenges, regulatory harmonization between OJK and LAPS, enhanced oversight of LAPS, the establishment of a digital complaint system, and clarification of OJK’s dispute resolution role are recommended. Additionally, strengthening electronic banking regulations through progressive liability principles, greater transparency, and simplified dispute resolution mechanisms is essential. Finally, reconstructing POJK 2022 to restore OJK’s facilitative function and enable intervention when LAPS proves ineffective is necessary to safeguard consumer protection.